MECHANICS OF MIXING OF PARTICLES IN THE PROCESS OF RE-PRODUCTION OF ASPHALT CONCRETE: DEFINITION OF FUNCTIONAL RELATIONS - N. S. Lyubimyi; A. D. Smitrovich; B. S. Chetverikov; A. V. Shekhovcov (Вестник СибАДИ)
Introduction. In order to save resources, in many countries of the world the raw materials’ re-use method is used. Machines such as recyclers are used to recycle asphalt concrete. The durability of the road surface depends on the quality of asphalt concrete mix. The process of mechanical mixing plays a very important role in the substance homogeneity obtained during the mixture production. Therefore, it is necessary to study the basic mechanism and method of mixing.Materials and methods. The authors used the basic laws of hydrodynamics and solved the equations of the similarity theory.Results. As a result, the authors considered the power by the mixer and the power that was necessary to obtain the desired quality of the mixture. The paper described the required number of revolutions of the stirrer for the preparation of suspensions and emulsions, taking into account the energy efficiency of the mixing process.Discussion and conclusions. The authors reveal that the basic equations of mechanical mixing of the medium depend on the power. Moreover, the authors built the graph of the mixing power and the graph of the Reynolds criterion for the main geometric parameters of the mixing organs.